Pengaruh Penyimpanan Suhu Refrigerasi terhadap Karakteristik Fisik Organoleptik, Nilai pH, Cemaran Coliform dan Salmonella spp., Yoghurt Susu Kambing dengan Penambahan Tepung Bekatul Beras Merah - Haskito, Ajeng Erika Prihastuti; Mahdi, Chanif; Mawarni, Riski Eka; Immauliate, Sinthia Medchera (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2024)
Yogurt is a fermented milk product made with the help of Lactic Acid Bacteria (LAB). Goat milk yogurt with the addition of red rice bran flour contains high antioxidants, making it very beneficial for health. This study aims to evaluate the effect of storage duration on the organoleptic physical characteristics, pH value, and contamination by Coliform and Salmonella spp. in goat milk yogurt with the addition of red rice bran flour. The study used 20 samples divided into five treatment groups based on storage duration (0, 1, 2, 3, and 4 weeks) at 4 ℃, with four repetitions. Each week, organoleptic physical characteristics were tested hedonically and hedonic quality assessed by 20 semi-trained panellists, pH measured with a digital pH meter, Coliform contamination tested using the Most Probable Number (MPN) method, and Salmonella spp. contamination tested using SSA media followed by TSIA media. Data analysis for organoleptic physical characteristics was conducted using the Kruskal-Wallis test followed by the Mann-Whitney test. Data analysis for pH and Coliform contamination was conducted using one-way ANOVA followed by the Tukey test. Data analysis for Salmonella spp. contamination was done descriptively. The results showed that the storage duration significantly affected the physical characteristics of appearance, taste, and aroma (p<0.05) but did not significantly affect colour (p>0.05). There were very significant differences in pH values and Coliform contamination (p<0.01), whereas Salmonella spp. contamination was not affected by the storage duration. The conclusion of this study is that goat milk yogurt with the addition of red rice bran flour should be consumed within three weeks based on organoleptic physical characteristics, pH value, and levels of Coliform and Salmonella spp. contamination.